THE IMPORTANCE OF SERVICE DELIVERY IN THE COMMUNITY - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Service quality can be determined by comparing the perceptions of consumers for the services that they obviously received the services that they expected to get through the attributes of an enterprise service. If the received service or perceived service is what they have expected, then the perceived service delivery is good and satisfactory. Moreover, if the received service is exceeding the consumers’ expectation, then the perceived service is excellent. While conversely, if the received service is lower than expected, then the perceived service is classified as a poor quality of service. Kotler (2002) explained that the definition of service is any action or activity that can be offered by one party to another, which is essentially intangible and does not result in any ownership; its production may be linked or not linked to a physical product. A service is the producer behavior carried out to meet consumer needs and desires in order to achieve customer satisfaction. Kotler also said that behavior could be occurred during, before or after the transaction. And these actions or activities are as explained below: